Investigation of graphite effect on the mechanical and tribological properties of Al 7075-SiC-graphite hybrid metal matrix composites - ATLA, SRIDHAR; Kaujala, Prasanna Lakshmi (Tribologia - Finnish Journal of Tribology, 2020)
The aluminium metal matrix composite reinforced with ceramic material of Silicon carbide (SiC) has good mechanical properties. However, aluminium based ceramic composites require improvements in their lubrication and tribological properties. In this study an attempt is made in the development of a new material through powder metallurgy technique by the addition of Graphite, which acts as a solid lubricant. This work investigated the inﬂuence of graphite on the wear behaviour of Al 7075/SiC /X wt.% graphite(X=0, 5 and 10) hybrid composite. The investigation reveals the effectiveness of incorporation of graphite in the composite for gaining wear reduction. The Al 7075 (aluminium alloy 7075) reinforced with SiC –graphite were investigated. The composites were fabricated using powder metallurgy route. The microstructures, material combination, wear and friction properties were analysed by scanning electron microscopy, XRD, and pin-on-disc wear tester. The newly developed aluminium composite has signiﬁcant improvements in tribological properties with a combination of 5% Silicon carbide (SiC) and 5% Graphite. The test reveals that sliding distance of 1000 m and sliding speed of 1.5 m/s with applied load of 5 N result in minimum wear loss of 0.01062g and coefficient of friction as 0.1278.